Slr1293 in Synechocystis sp. Strain PCC 6803 Is the C-3′,4′ Desaturase (CrtD) Involved in Myxoxanthophyll Biosynthesis - Mohamed, Hatem E. (American Society for Microbiology, 2004)
When grown at high light intensity, more than a quarter of the total carotenoids in the unicellular cyanobacterium Synechocystis consists of myxoxanthophyll, a polar carotenoid glycoside. The biosynthetic pathway of myxoxanthophyll is unknown but is presumed to involve a number of enzymes, including a C-3′,4′ desaturase required to add one double bond to generate 11 conjugated double bonds in the monocyclic myxoxanthophyll. A candidate for this desaturase is Slr1293, which was identified by genome similarity searching. To determine whether Slr1293 is a desaturase recognizing neurosporene and lycopene, slr1293 was expressed in Escherichia coli strains accumulating neurosporene or lycopene. Confirming such a desaturase function for Slr1293, these E. coli strains accumulated 3′,4′-didehydroneurosporene and 3′,4′-didehydrolycopene, respectively. Indeed, deletion of slr1293 in Synechocystis provides further evidence that Slr1293 is a desaturase recognizing neurosporene: In the slr1293 deletion mutant, neurosporene was found to accumulate and was further processed to produce neurosporene glycoside. Neurosporene hereby becomes a primary candidate to be the branch point molecule between carotene and myxoxanthophyll biosynthesis in this cyanobacterium. The slr1293 gene was concluded to encode a C-3′,4′ desaturase that is essential for myxoxanthophyll biosynthesis, and thus it was designated as crtD. Furthermore, as Slr1293 appears to recognize neurosporene and to catalyze the first committed step on the myxoxanthophyll biosynthesis pathway, Slr1293 plays a pivotal role in directing a portion of the precursor pool for carotenoid biosynthesis toward myxoxanthophyll biosynthesis in Synechocystis sp. strain PCC 6803.